Komparasi TOPSIS dan Weighted Product Dalam Pengambilan Keputusan Pada Penentuan Susunan Personalia Organisasi - Ahmadi Irmansyah Lubis; Rezi Elsya Putra; Supinah (Ikatan Ahli Informatika Indonesia, 2025)
The determination of the composition of personnel in an organization, especially in the Branch Meeting (Musran) of the Muhammadiyah Branch Executive (PRM) of Sungai Panas Village, is still carried out manually and tends to be subjective. This has the potential to cause inefficiencies and internal conflicts in the decision-making process. This research aims to develop a web-based Decision Support System (SPK) that can help the management selection process objectively and systematically through the comparison of two Multicriteria Decision Making (MCDM) methods. The process of weighting criteria is carried out objectively using the Rank Order Centroid (ROC) method. Furthermore, the ranking of prospective administrators was carried out using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Weighted Product (WP) methods to test the accuracy and suitability of the results. The five main criteria used include: organizational experience, level of education, loyalty to the organization, leadership, and availability of time. The system is designed using the PHP programming language and MySQL database. The results of the implementation show that the system is able to produce recommendations for a more systematic, transparent, and accountable management structure, as well as provide a clear comparison of results between TOPSIS and taxpayers. With this SPK, the deliberation process can run faster and more efficiently, as well as strengthen democratic data-based organizational governance.